Analisis Pengaruh Digital Marketing Terhadap Peningkatan Penjualan UMKM di Era Pasca Pandemi - Sudarynianto Nurathaya Sutarto; Hwihanus Hwihanus (Jurnal Manajemen dan Ekonomi Kreatif, 2025)
This study aims to analyze the influence of digital marketing on increasing sales of Micro, Small, and Medium Enterprises (MSMEs) in the post-pandemic era. Along with technological developments and changes in consumer behavior, MSMEs are faced with the challenge of adopting digital marketing strategies to increase competitiveness and maintain business continuity. This study uses a quantitative method with data collection through a survey of 100 MSME actors in various sectors. The data obtained was analyzed using multiple linear regression to determine the relationship between digital marketing variables (social media use, marketplace, and paid advertising) to increase sales.